Warren, Milley & Foote. (1916)
1 photograph : sepia toned 13.5 x 7.5 cm William Robertson Warren, Samuel F. Milley and Samuel J. Foote sitting on the front step of Fomowa Fishing Club. Title from album caption. William Robertson Warren (1879-1927), son of William Henry and Jessie (Harvey) Warren, was born in St. John's in 1879. He began his political career in 1903, and became Prime Minister of Newfoundland from July 1923 - April 1924. Warren died suddenly on December 31, 1927. Samuel F. Milley (1867-1939) was born in St. John's in 1867. Milley was a prominent dry goods merchant in St. John's from 1890's and was a member of the Legisaltive Council for more than 30 years. Milley died in Montreal on February 12, 1939. Samuel J. Foote (1873-1936) was born in Grand Bank in 1873. Foote was called to the Newfoundland Bar in 1899 and went to practice with Sir James Winter. Foote entered into politics in 1904. Foote died on December 8, 1936. Good An album containing 323 black and white photographs and 25 pages of text, covering the years 1914 to 1937 of the FOMOWA Fishing Club on the Grand Codroy River on the west coast of Newfoundland. The album's images have been digitized as separate items.